The Correlation Between Learning Environment and Motivation on the Development of Students Speaking Skills at Ma Nwdi Gereneng - Nazri, Adib; Fikni, Zahratul; Riana, Linda; Prasetyaningrum, Ari (Journal of English Language and Education, 2025)
This study aims to examine the correlation between the learning environment and motivation on students’ speaking skills at MA NWDI Gereneng. Speaking is one of the essential components in English language learning, requiring not only linguistic mastery but also psychological support and a motivating environment. This research applied a quantitative correlational method involving 20 eleventh-grade students. The instruments used were a learning environment questionnaire, a motivation questionnaire, and a speaking test assessed through four indicators: fluency, accuracy, interaction, and comprehensibility. Data were analyzed using Pearson correlation and multiple linear regression. The results showed a very strong and significant correlation between the learning environment and speaking skills (r = 0.975, p 0.01), and between motivation and speaking skills (r = 0.950, p 0.01). Simultaneously, both variables significantly influenced students’ speaking performance, with a determination coefficient (R²) of 0.976. This means that 97.6% of the variation in students’ speaking skills can be explained by their learning environment and motivation. These findings emphasize the importance of a supportive, engaging classroom environment, along with the development of both intrinsic and extrinsic motivation, in enhancing students’ speaking ability in English. Teachers and schools should focus on creating positive classroom conditions and encouraging student motivation to support the success of English language learning.